2019
DOI: 10.3233/jad-181220
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Alteration and Its Time Course in a Tauopathy Mouse Model

Abstract: Emerging evidence suggests that gut microbiota dysbiosis plays a role in neurodegenerative disorders. However, whether the composition and diversity of the gut microbiota are altered in tauopathies remains largely unknown. This study was aimed to examine the diversity and composition of the gut microbiota in tauopathies, as well as the correlation with pathological changes in the brain. We collected fecal samples from 32 P301L tau transgenic mice and 32 age-and gendermatched littermate mice at different ages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 56 publications
5
29
0
Order By: Relevance
“…Our results agree with those reported by Bonfili et al (2017) , where they show no differences in alpha diversity in 3xTg-AD mice at 2, 3, 4.5, and 6 months old. This same effect was observed in P301L tau transgenic mice at 1, 3, and 6 months old ( Sun et al, 2019 ). However, it has been demonstrated that 9 months old 3xTg-AD mice showed lower alpha diversity than NoTg mice ( Syeda et al, 2018 ).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Our results agree with those reported by Bonfili et al (2017) , where they show no differences in alpha diversity in 3xTg-AD mice at 2, 3, 4.5, and 6 months old. This same effect was observed in P301L tau transgenic mice at 1, 3, and 6 months old ( Sun et al, 2019 ). However, it has been demonstrated that 9 months old 3xTg-AD mice showed lower alpha diversity than NoTg mice ( Syeda et al, 2018 ).…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, we observed a decrease in the relative abundance of TM7 in female and male 3xTg-AD mice at 3 and 5 months old in comparison to NoTg mice, while an increase was found in the relative abundance of Fusobacteria and Cyanobacteria in female and male 3xTg-AD mice at 5 months old in comparison to NoTg mice. This effect has been also reported in P301L mice, a tauopathy model at 3 and 6 months old ( Sun et al, 2019 ), and in AD patients ( Vogt et al, 2017 ). Also, a decrease in relative abundance in both TM7 and Cyanobacteria has been documented in female 3xTg-AD mice at 9 months old ( Syeda et al, 2018 ).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Wang et al (2015) demonstrated that exposure to Helicobacter pylori filtrate induces Alzheimer-like tau hyperphosphorylation by activating glycogen synthase kinase-3β (GSK-3β). Sun et al (2019a) also found that decrease in abundance of gut bacteria such as Marvinbryantia, Lactobacillus, Streptococcus, unclassified_Erysipelotrichaceae, and Eubacterium_brachy_group were negatively correlated with tau pathology in the brain in a tauopathy model, suggesting that the decrease in these microbiota may be closely related to the severity of tauopathies. Recently, Wei et al (2020) found that outer membrane vesicles, produced by the gut microbiota, increase the permeability of the BBB and promote the activation of astrocytes and microglia, inducing an inflammatory response and tau hyperphosphorylation by activating the GSK-3β pathway, ultimately leading to cognitive impairment.…”
Section: Aβ and Tau Phosphorylation Pathwaysmentioning
confidence: 80%
“…Both higher ( 44 , 49 , 52 ) and lower ( 45 , 51 ) abundance was reported of the phylum Firmicutes in AD mouse models. Families and genera that contain butyrate-producing species like the family Lachnospiraceae ( 49 , 51 , 52 ) and the genus Roseburia ( 50 52 ) were also both increased and reduced in AD mice compared to WT. Notably, the butyrate-producing genus Ruminococcus was either unchanged or decreased ( 46 , 47 , 49 ).…”
Section: Microbiota Composition In Ad Patients and Ad Animal Modelsmentioning
confidence: 90%